Limiting values of slenderness ratio for circular braces of concentrically braced frames. (December 2015) - Kumar, P.C. Ashwin; Sahoo, Dipti Ranjan; Kumar, Nitin
Abstract: Special concentrically braced frames (SCBFs) are commonly used to resist lateral forces in the structures located in high-seismic regions. Steel braces of SCBFs are expected to undergo large inelastic axial deformations in order to provide an adequate level of structural ductility and hysteretic energy dissipation under cyclic loading. The energy dissipation capacity and ductility of SCBFs largely depend on the slenderness ratio and width-to-thickness ratio of braces. The main objective of this study is to find an optimum range of these parameters for braces of hollow circular steel (HCS) sections in order to achieve the enhanced seismic performance of SCBFs. A finite element (FE) study has been conducted on a wide range of values of these parameters using a software package ABAQUS. The FE models account for the inelastic hysteretic characteristics and the fracture behaviour of braces. The results of simulation models matched very well with the past experimental results with respect to the performance points, namely, global buckling, local buckling, fracture initiation, and complete fracture. Finally, a relationship has been established between the slenderness ratio and the width-to-thickness of HCS braces based on the simulation results. Highlights: The lower and upper limits of slenderness ratio depend on the compactness ratio. The maximum value of D / t ratio for hollow circular braces should be 18.5. The minimum value of brace slenderness ratio should be less than 90. The minimum slenderness ratio for HCS braces should be 110 for D / t equal to 20.